Self-ratings of Spoken Language Dominance: A Multi-Lingual Naming Test (MINT) and Preliminary Norms for Young and Aging Spanish-English Bilinguals() - Gollan, Tamar H. (2012)
This study investigated correspondence between different measures of bilingual language proficiency contrasting self-report, proficiency interview, and picture naming skills. Fifty-two young (Experiment 1) and 20 aging (Experiment 2) Spanish-English bilinguals provided self-ratings of proficiency level, were interviewed for spoken proficiency, and named pictures in a Multilingual Naming Test (MINT, and in Experiment 1 also the Boston Naming Test; BNT). Self-ratings, proficiency interview, and the MINT did not differ significantly in classifying bilinguals into language-dominance groups, but naming tests (especially the BNT) classified bilinguals as more English-dominant than other measures. Strong correlations were observed between measures of proficiency in each language and language-dominance, but not degree of balanced bilingualism (index scores). Depending on the measure, up to 60% of bilinguals scored best in their self-reported non-dominant language. The BNT distorted bilingual assessment by underestimating ability in Spanish. These results illustrate what self-ratings can and cannot provide, illustrate the pitfalls of testing bilinguals with measures designed for monolinguals, and invite a multi-measure goal driven approach to classifying bilinguals into dominance groups.